2016
DOI: 10.1063/1.4950882
|View full text |Cite
|
Sign up to set email alerts
|

Band offset at the heterojunction interfaces of CdS/ZnSnP2, ZnS/ZnSnP2, and In2S3/ZnSnP2

Abstract: Band gap of sphalerite and chalcopyrite phases of epitaxial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Hence, the large series resistance comes from resistances at the interfaces of CdS/ZnSnP 2 and/or ZnSnP 2 /Mo, and the further investigation is necessary to clarify the effect of interfaces. On the other hand, the small value of the open‐circuit voltage, V OC , 0.172 V, might be attributed to the large conduction band offset (CBO) between CdS and ZnSnP 2 , −1.2 eV , which makes a cliff at their interface and limits the value of V OC . In the viewpoint of the conduction band offset, it was suggested that ZnS and In 2 S 3 were suitable materials as a buffer layer.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the large series resistance comes from resistances at the interfaces of CdS/ZnSnP 2 and/or ZnSnP 2 /Mo, and the further investigation is necessary to clarify the effect of interfaces. On the other hand, the small value of the open‐circuit voltage, V OC , 0.172 V, might be attributed to the large conduction band offset (CBO) between CdS and ZnSnP 2 , −1.2 eV , which makes a cliff at their interface and limits the value of V OC . In the viewpoint of the conduction band offset, it was suggested that ZnS and In 2 S 3 were suitable materials as a buffer layer.…”
Section: Resultsmentioning
confidence: 99%
“…For Pb-PSCs, the CBO at the ETL/perovskite layer interface is close to zero when TiO 2 or fullerenes are used to form the ETL. However, Sn-based perovskite materials have been reported to have lower electron affinities than Pb-based perovskite materials. , Therefore, the CBO at the ETL/perovskite layer interface is high when these common ETL materials are used. The energy band offset at the heterojunction interface generally affects the V OC in solar cells such as Cu­(In,Ga)­Se 2 (CIGS) and Cu 2 ZnSnS 4 (CZTS) solar cells. Minemoto et al investigated the relationship between the V OC and the CBO at the ETL/perovskite layer interface theoretically for a p-i-n heterojunction device composed of Sn–Ge mixed perovskites and showed that the CBO had a strong influence on the V OC . However, their work did not compare Sn-PSCs and Pb-PSCs and it thus remains unclear why the Sn-PSCs have a comparatively large V OC loss.…”
Section: Introductionmentioning
confidence: 99%
“…In this device, the value of V OC was significantly low considering the bandgap of ZnSnP 2 . XPS measurements revealed that CdS/ZnSnP 2 showed a large conduction band offset, ΔE C = −1.2 eV, 24 which suggested that band alignment was necessary to achieve a high conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%